External match load and the influence of contextual factors in elite futsal - Spyrou, Konstantinos; T. Freitas, Tomás; Marín-Cascales, Elena; Herrero-Carrasco, Rubén; E. Alcaraz, Pedro (Biology of Sport, 2022)
Quantifying external load during futsal competition can provide objective data for the management of the athlete’s performance and late-stage rehabilitation. This study aimed to report the match external load collected via wearable technology according to time periods (i.e., halves) and contextual factors (i.e., team’s ranking, match result, and location) in elite futsal. Nine professional male players used a GPS-accelerometer unit during all games of the 2019–2020 season. Player load (PL), PL·min-1, high-intensity acceleration (ACCHI), deceleration (DECHI), explosive movements (EXPL-MOV), and change of direction (CODHI) data were collected. On average, players displayed values of: total PL 3868 ± 594 a.u; PL·min-1: 10.8 ± 0.8 a.u; number of ACCHI: 73.3 ± 13.8, DECHI: 68.6 ± 18.8, EXPL-MOV: 1165 ± 188 and CODHI: 173 ± 29.1. A moderate and significant decrease was found in the 2nd half for total PL (p = 0.03; ES = 0.52), PL·min-1 (p = 0.001; ES = 1.16), DECHI (p = 0.001; ES = 0.83), and EXPL-MOV (p = 0.017; ES = 0.58) compared to the 1st half. Small and nonsignificant differences were found between contextual factors. In summary, this study indicates that futsal players are exposed to high-intensity mechanical external loads, and perform a great number of ACCHI, DECHI, EXPL-MOV and CODHI, without being influenced by the team ranking, result and match location. Coaches and sports scientists are advised to implement speed-power, DEC, and COD activities in the training sessions, and may use these reference values to design specific training and return-to-play plans.